2019
DOI: 10.1161/circep.118.007118
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Percutaneous Stellate Ganglion Blockade in Patients With Electrical Storm

Abstract: Background: Percutaneous stellate ganglion blockade (SGB) has been used for drug-refractory electrical storm due to ventricular arrhythmia (VA); however, the effects and long-term outcomes have not been well studied. Methods: This study included 30 consecutive patients who had drug-refractory electrical storm and underwent percutaneous SGB between October 1, 2013, and March 31, 2018. Bupivacaine, alone or combined with lidocaine, was injected into the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…Sympathetic denervation has shown to relieve electrical storm suggesting sympathetic activation may play an important role in occurrence of ventricular fibrillation 19 21 and prior studies demonstrated that sympathetic nervous system is activated in AF patients and has critical role in AF development 22 . Furthermore, AF is associated with significant patient discomfort which might activate sympathetic tone 2 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic denervation has shown to relieve electrical storm suggesting sympathetic activation may play an important role in occurrence of ventricular fibrillation 19 21 and prior studies demonstrated that sympathetic nervous system is activated in AF patients and has critical role in AF development 22 . Furthermore, AF is associated with significant patient discomfort which might activate sympathetic tone 2 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the SGB to improve blood flow and deactivate sympathetic tone has also been useful in the treatment of Raynaud's phenomenon and hyperhidrosis in the upper limbs ( Rickles, 1977 ). Currently SGB is showing promise for treatment of post-traumatic stress disorder ( Lipov et al, 2012 ; Mulvaney et al, 2014 ), cardiac arrhythmia ( Tian et al, 2019 ), and hot flashes associated with cancer treatment and menopause ( Othman and Zaky, 2014 ; Rahimzadeh et al, 2018 ). Mechanisms for the durable central nervous system effects of the SGB in these conditions are unclear, delaying its broad acceptance as a valid treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The role of unilateral left sided vs bilateral SGB continues to evolve. Prospective analyses have shown similar efficacy between the 2 ( 9 ). Although the left-sided SGB has been shown to reduce ventricular fibrillation threshold following myocardial infarction, functional asymmetry of the stellate ganglia suggest a role of the right stellate ganglion in influencing heart rate and arrhythmia vulnerability.…”
Section: Discussionmentioning
confidence: 90%